THE FUTURE POTENTIAL OF TOURISM IN LANGKAWI, MALAYSIA: PREDICTION USING THE DELPHI METHOD - MOHD. SHARIFF, NURHAZANI; ZAINOL, NOOR AZIMIN; MOHD NOR, NOR ASHIKIN (ITB Journal Publisher, LPPM ITB, 2006)
This article presents the findings of a study regarding the prediction of tourism in Langkawi by using the Delphi Method. The study was conducted for the purpose of testing and implementing the Delphi Method as a qualitative method in predicting the future potential of tourism in Langkawi through the perceptions and evaluations of the tourism experts.Eight respondents were selected as judges in the study. The consensuses among the panel judges were reached only in the second-round of the questionnaire distribution. Thus, the findings indicated that the Delphi Method is an effective method to predict the future potential of tourism in Langkawi from 2003 through to 2010. Several items in the community value systems and the tourism structures increased in parallel to the growth of the Langkawi tourism industry from 2003 through to 2010. This consequently would lead to a communitypositive acceptance toward the changes occurred in their areas. The panel judges also agreed that Langkawi has a potential to become an international tourist destination and an international tourism events and conference destination to the year 2010. Thus, it is suggested that-items which increase in parallel to the growth of tourism to be taken into consideration in planning and implementing the tourism strategy for the future.